Pengaruh Penerapan Model Interactive Conceptual Instruction (ICI) terhadap Hasil Belajar Peserta Didik Kelas VII di SMPN 34 Padang - Putri, Widya Forisya; Yurnetti; Diliarosta, Skunda; Yanto, Febri (SEMESTA: Journal of Science Education and Teaching, 2025)
Low students learning outcomes are often attributed to conventional teacher-centered instructional methods, which render students passive and hinder their ability to comprehend and apply scientific concepts effectively. This study aims to evaluate the effect of the Interactive Conceptual Instruction (ICI) learning model on the academic performance of seventh-grade students at SMPN 34 Padang, specifically in the topic of substance classification and changes. This research employed a quasi-experimental design using a posttest-only control group approach. The sample consists of two classes, an experimental group that received instruction using the ICI model and a control group that followed conventional methods. Data were analyzed statistically using Microsoft Excel. The results indicate that the average posttest score of the experimental group (77) was higher than that of the control group (65). A t-test analysis yielded a tcount of 5.303, which exceeds the critical ttable of 1.998, indicating a statistically significant difference between the two groups. The implementation of the ICI model was rated positively, with an effectiveness score of 98%, and 94% of students responded favorably to the learning model. In conclusion, the study demonstrates that the application of the ICI model has a significant positive impact on students' learning outcomes in the topic of substance classification and changes.